Evaluación de los aprendizajes de las matemáticas desde un enfoque constructivista por competencias en los estudiantes de tercer año de básica de la Escuela de Educación Básica Ecuador Parroquia la Unión, cantón Babahoyo, provincia los Ríos - Lamán Figueroa, Cecilia Gabriela (2017)
The evaluation of learning is a constant process of information production for decision making, on the improvement of the quality of education in a social human context, through its diagnostic, formative and summative functions. In the last twenty years the curriculum has proposed for the system of formal education up to diversified education epistemological approaches that are oriented towards humanism and constructivism, along with academic rationalism. However, in the evaluation practice a normative approach prevails, where it deprives the measurement of contents and the formative evaluation processes are left aside. In other words, in order for the curriculum to change, the evaluation practice must also change and vice versa. To rethink the curriculum from an interdisciplinary point of view it is necessary to take into account the presence of the essential, the essential, the unpronounceable and download it from the excess of content that currently characterizes most educational systems, to give a twist to the evaluation from the inflexible and normative to the competency-based approach